The Lenses and Experiences of Grade 10 English Teachers on Distance Learning Modalities: A Phenomenological Study (International Journal of Theory and Application in Elementary and Secondary School Education, 2021)
The qualitative existential-phenomenological study aimed to determine, describe, and investigate the perspective and experiences of the English Teachers on the implementation of distance learning modality using appreciative inquiry (AI) as its organizing principle. The participants were Grade 10 English teachers and selected students from public high schools in the Division of Santa Rosa City, Laguna, Philippines. Specifically, it addressed two central objectives: determine the best and most positive perspective and experiences of the English teachers in the implementation of distance learning modalities and determine the futuristic views of the English teachers on distance learning modalities for its successful implementation. As to the best and most positive lenses and experiences of the English teachers of Grade 10 English teachers on distance learning modalities, there were 20 themes generated. Likewise, as to the futuristic views of the English teachers on distance learning modalities for its successful implementation, 19 themes were developed. Based on the results, several factors that contribute to the development of the positive value system were identified through phenomenological analysis, including personal-related factors, peer-related factors, administration-related factors, stakeholders-related factors, and resources-related factors.